Health Systems in times of coronavirus - Casavilca-Zambrano, Sandro (2020)
The Peruvian State has declared 2020 as the "Year of Universal Health", expressing a desire and right of all Peruvians, as set forth in the Political Constitution of Peru (1). Traditionally, health is conceived as "absence of disease", the latter being understood as a state of alteration of the organism, which disturbs its normal functioning. In 1947, the World Health Organization (WHO), in its Magna Carta, defined health in positive terms as "the state of complete physical, mental and social well-being", and not merely as the absence of disease. From this conviction has emerged a new vision of health, called the biopsychosocial model, moving away from the thesis that to speak of health is to speak of disease.